Manajemen dan Administrasi tentang Pengolahan Limbah di Industri Perkapalan: Tinjauan Literatur, Pengelolaan Informasi dan Tantangan Masa Depan - Muhammad Zaki Raihansyah; Deswitha Kamilia Rachman; Devi Intan Aryani; Aisyah Dwi Ayu Firdaus; Denny Oktavina Radianto (Universitas 17 Agustus 1945, 2024)
Waste management in the maritime industry is a crucial aspect in maintaining environmental and operational sustainability of the industry. In this context, a literature review becomes essential to understand best practices, challenges, and potential solutions in waste management in the maritime industry. This research aims to present a comprehensive literature review on waste management in the maritime industry, focusing on management practices and future challenges. The literature review includes mapping of theoretical concepts, explanation of effective management practices, and analysis of relevant waste treatment technologies. Findings from this literature review provide an in-depth understanding of the complexity of waste management in the maritime industry, the crucial role of management in addressing these challenges, and the urgency in facing increasingly stringent environmental regulations. The implications of this literature review include emphasis on the importance of developing environmentally friendly technologies, collaboration between governments and industries, and awareness of the interconnection between waste management and sustainability goals. This research is expected to provide valuable guidance for the maritime industry in enhancing their waste management practices, thus creating a more sustainable future for the industry and the environment as a whole.